ANALISIS PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP TINGKAT PENGUNGKAPAN RISIKO PADA PERUSAHAAN MANUFAKTUR - Yunifa, Latifah; Juliarto, Agung (Diponegoro Journal of Accounting, 2017)
The purpose of this study is to analyze the effect of firm characteristics such as firm size, leverage, profitability, liquidity, complexity, and type of auditor to the level of corporate risk disclosure. Risk disclosure is disclosures made by the company with regard to the opportunities or prospects, danger, threat or exposure, which may have an impact on the company, and management opportunities, prospects, dangers, threats or the exposure. To explain the relationship between variables in this study, use of agency theory and signaling theory. The population of this study are all manufacture companies listed on the Indonesia Stock Exchange period 2015. Total sample of 94 companies was determined by purposive sampling method. Content analysis method used to calculate the risk disclosures by counting the number of sentences that relate to risk category in the annual report. There are seven categories of risk disclosures used in this study, namely a general risk information, accounting policies, financial instruments, derivatives hedging, reserves, financial and other risks and commodity risks. The method used to test the hypothesis is multiple regression analysis.The results show that the category’s mean of risk disclosures sentences in non-financial companies was 39 sentences. The category of risk disclosure that most widely performed by the companies is accounting policy category. The results of hypothesis testing showe that company size, leverage, profitability, liquidity, and complexity affect the level of risk disclosure. While auditor type do not affect the levels of risk disclosure.